COMPARISON OF INTEGRATION RESULTS OF HETEROGENEITY INDEX ANALYSIS WITH QUALITY MAPS ON SINGLE AND MULTI RESERVOIRS - Tri Candra A.H., Julian
Developing and optimizing mature field is one strategy that can be carried out to increase the cumulative production of oil and gas in the country considering that the number of mature fields in Indonesia continues to increase. Integrated static and dynamic data is needed as a basis for considerations for reservoir engineers in forming development strategies and optimizing oil and gas resources in mature fields. Therefore, this study was conducted to determine the relationship between production data that has been processed using the heterogeneity index method and reservoir static data in the form of quality maps for each parameter consisting of the Simulation Opportunity Index (SOI), Well Opportunity Index (WOI) and reservoir property parameters, such as oil saturation, hydrocarbon pore volume, movable pore volume, permeability, and Reservoir Quality Index (RQI) using actual models. This study begins with the availability of two reservoir simulation model data, namely single reservoir models (Field "G") and multi reservoir (Field "M") which will later be simulated based on different cases. There are two cases that will be carried out in this study's reservoir simulation model, namely history matching/constraint production data to represent actual conditions and forecasting using bottomhole pressure constraints to determine the relationship between the heterogeneity index and the quality maps. Followed by analysis of the heterogeneity index, quality maps generation, lumping of all layers in the quality maps, and ending with an overlay analysis of the heterogeneity index and quality map for each case in each field. The heterogeneityindex can only be related to the quality maps if the HI parameter is changed to alpha (?). If pure HI formula is used, the largest R2 of HI with quality maps is only 0.5514. Meanwhile, if converted into alpha (?) we get R2 in a single reservoir field for the parameters of permeability, RQI, oil saturation, HCPV, MOPV, WOI, and SOI spatially at 0.3333, 0.3495, 0.5003, 0.4957, 0.5632, 0.5899, and 0.8378, respectively. The R2 value or the relationship between the SOI quality map and the quantitative heterogeneity index in a multi-reservoir field still shows a very small value, that is 3 x 10-6. The parameter with the highest R2 value when compared with other parameters in single reservoir fields that still use pure HI is SOI, that is 0.5514. Meanwhile, if converted into alpha (?), the highest R2 is obtained at 0.8378 for the SOI parameter